Tracing Trajectories of Regime Support in Turkey - Inan, Murat (Ege Univ, Fac Economics & Admin Sciences, 2022)
According to the legitimacy approach of political culture research, public's approval of a particular regime as the best form of government and rejection of its alternatives provides public support for that particular regime. This research attempted to trace temporal trajectories of approval of democratic political system as well as it's three alternative forms of government among the electorates of recent three major political parties in Turkey, the Justice and Development Party (AKP), the Republican People's Party (CHP) and the Nationalist Movement Party (MHP). It also revealed the extent these parties' manifesto documents praise democratic political system across the successive eighteen general elections in the modern Turkish political history. It revealed the changes in both public and party support for four alternative regimes across years in modern Turkish history. This research analyzed the World Values Survey and the Manifesto Project data using quantitative research methods. It has achieved four main findings. First, voters are more stable than their parties across time in terms of pro-democracy. Second, democracy clearly emerges as the strongest alternative among the four alternative regimes for all the three electorates. Third, supporting democracy and rejecting its three alternatives occupy different places in the minds of the three party electorates. Fourth, changes in the three political parties' pro-democracy as identified in their manifesto documents are not always parallel with changes in those of their voters.
Keywords: Political Regime; Political Culture; Legitimacy Approach; Democracy; Party Politics; Sosyoloji; Siyasi Bilimler